Post-Divorce Adjustment in Divorced Madurese Women - Muqoddam, Faqihul; Ishlakhatus Sa'idah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
The prevalence of divorce in Madurese society has increased in recent years, and the party that feels the most impact of divorce is women. This study aims to explain the adjustment of Madurese women after divorce. This study uses a qualitative method with a Phenomenological approach. Data collection used in-depth interview techniques involving 13 Madurese women who had divorced. Data were analyzed using the Interpretative Phenomenological Analysis (IPA) technique which involved eight stages of data analysis. Data credibility was carried out using the member check technique. The results of the study showed two themes, namely emotional dynamics and post-divorce adjustment in Madurese women. The emotional dynamics of divorced Madurese women include loneliness, sadness, hopeless, disappointment, regret, pessimism, and relief. Meanwhile, the post-divorce adjustment process that they do includes seeking social support, busying themselves with various activities, getting closer to God through prayer and worship, trying to divert memories, regulating emotions, and rebuilding self-confidence. This study is useful for Madurese women as a basis or guideline in making adjustments after divorce. It is also important to understand that the role of close people can contribute greatly to helping divorced women adjust.